Manajemen Strategi Penanggulangan Bencana Banjir Bandang Oleh BPBD Kabupaten Pasaman - Taufani Ahmad; Roni Ekha Putera; Yoserizal Yoserizal (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
This study aims to analyze and describe the management of flash floods disaster management strategies carried out by BPBD Pasaman Regency. This research is motivated by Pasaman Regency which is a disaster-prone area. flash floods is one type of disaster that has a high potential and has a large impact and loss. Thus, there is a need for a strategic management process carried out by the Pasaman Regency BPBD in the implementation of flash floods disaster management which aims to reduce the risk of flash floods disasters in Pasaman Regency. The method used is descriptive qualitative, with data collection techniques using interviews, documentation, and observation. . The selection of informants was done by purposive sampling technique. The data analysis technique used in this study according to Miles and Huberman, meanwhile to test the validity of the data obtained in the field, the source triangulation technique was used. The strategic management process is carried out by describing the phenomena found in the field using the theory of J. David Hunger and Thomas L. Wheelen which states that the strategic management process consists of a process of environmental scanning, strategy formulation, strategy implementation and evaluation and control. The results of this study conclude that the strategic management process in flash floods disaster management by BPBD Pasaman Regency has not been achieved optimally, this is due to limited human resources owned by BPBD Pasaman Regency in terms of number and competence, lack of infrastructure facilities owned by all programs and activities optimally in achieving organizational goals, low presentation of budget realization in the implementation of programs and activities carried out, achievement of performance targets that are not yet optimal and special evaluations held by BPBD Pasaman Regency related to several activities in disaster management.